Utility of Flow Cytometry and Fluorescence In Situ Hybridization in Follow-up Monitoring of Plasma Cell Myeloma. Issue 2 (13th January 2021) - Chopra, Saurav; Dunham, Timothy; Syrbu, Sergei I; Karandikar, Nitin J; Darbro, Benjamin W; Holman, Carol J
Abstract: Objectives: We sought to investigate the clinical utility of flow cytometry (FC) and fluorescence in situ hybridization (FISH) in the workup of myeloma. Methods: We retrospectively reviewed the reports of bone marrow biopsies received for myeloma evaluation between October 2015 and January 2019. Results: A total of 1, 708 biopsy specimens from 469 myeloma patients (mean age, 64.5 years [SD, 9.3]; female, 41.4%) were reviewed. Both FC and FISH had comparable detection rates at the time of initial diagnosis (97.6% vs 98.8%) and for follow-up cases (28.6% vs 28.2%). FC and FISH results were concordant in 98.8% of the initial diagnosis cases and 89.6% of the follow-up cases. The FISH-positive (FISH+)/FC-negative (FC−) discordance and FISH−/FC+ discordance occurred among 81 (5.0%) and 87 (5.4%) follow-up cases. In comparison with all concordant cases, FISH+/FC− discordant cases were more likely to have received treatment with daratumumab ( P < .05). Conclusions: Plasma cell–enriched FISH and FC have comparable abnormal plasma cell detection rates, and approximately 10% of the follow-up cases have discordant FISH and FC results in which residual disease is detected by only one of these modalities. FISH testing should be considered for cases with negative FC, especially in patients who have received treatment with daratumumab or in cases in which there is concern about specimen adequacy.